Trading Zones of Digital History - Kemman, Max (Studies in Digital History and Hermeneutics, 2021)
Will historians become programmers? How do historians collaborate with experts from computational domains? At the centre of the book is the question how historians are affected by such ongoing interactions. By following historians and studying digital history collaborations, Kemman critically discusses how digital history will impact historical scholarship.